Alternative Global Layered Cellular Designs for a Blood Sugar Strip Manufacturer - Gursel A. Suer; Jue Jiang (International Journal of Supply Chain Management, 2017)
This paper discusses alternative supply chain design strategies for a global blood sugar strip manufacturing company. Two main alternatives considered are: 1) Single location manufacturing plant to meet world demand located in China; 2) three manufacturing plants located in three regions to meet world demand, China for Asian market, Ireland for European market and Puerto Rico for North American market. Manufacturing plants are designed considering layered cellular design approach under stochastic demand. This approach allows three types of cells to be formed: 1) dedicated cells for families, 2) shared cells, cells to be shared by two families, 3) remainder cells, cells to be used by three or more families. The main focus of this paper is to compare both alternatives by considering labor costs, machine investment costs and transportation costs. We will also discuss detailed operational control issues in one of the plants and discuss simulation results to validate the results obtained through layered design methodology. The results show that single manufacturing plant option is a more economical option.